Perubahan Perilaku Masyarakat Terhadap Kepatuhan Menjalankan Protokol Kesehatan Setelah Dilakukan Penegakan Disiplin Oleh Satpol PP - Susdarwono, Endro Tri; Susdarwanto, Eko (Journal of Humanity Studies, 2022)
This study aims to provide a description of changes in people's behavior towards compliance with health protocols after discipline is enforced by Satpol PP based on Tegal Regent Regulation No. 62 of 2020. In this study, the approach used was a combination of qualitative and quantitative. A qualitative approach is used to describe whether the enforcement of discipline carried out by Satpol PP related to compliance with health protocols results in changes in community behavior, while the quantitative approach used is hypothesis testing on signs used to analyze changes in community behavior compliance in carrying out health protocols after enforcement. disciplined by Satpol PP, while in order to ensure whether or not there is a change in the state of compliance with community behavior in carrying out health protocols, before and after treatment (before and after treatment research design) a hypothesis testing method on growth is used using the Mac Nemar change test. The enforcement of discipline carried out by the Satpol PP on compliance with community behavior in carrying out health protocols as an effort to overcome the spread of Covid 19 in Tegal Regency is able to make changes to people's behavior in carrying out health protocols for the better. This conclusion is obtained from statistical testing which states that from this study (1) the enforcement of discipline by Satpol PP can increase the level of compliance of community behavior in carrying out health protocols in Tegal Regency, (2) there is a change in the state of compliance with community behavior in carrying out health protocols in Kabupaten Tegal. Tegal after the enforcement of discipline by the Tegal Regency Satpol PP.